Spirex: SPUB indent ubat express - Mahayudin, Ahmad Fathi; Abd Halim, Afif; Ibrahim, Suryani; Ismail, Muhd Hamdi; Nasruddin, Farah Aina; Mohd Yusuf Authors, Mohd Yasharudin (2025)
Sistem Pendispesan Ubat Bersepadu (SPUB) is an initiative aimed at ensuring uninterrupted medication supply to patients. It is especially favored by patients receiving treatment at specialist hospitals in Kedah, such as Hospital Sultanah Bahiyah and Hospital Sultan Abdul Halim. SPUB allows patients to collect follow-up medications from nearby district hospitals or health clinics, promoting accessibility and continuity of care. However, due to the absence of a Pharmacy Information System (PhIS) at these major hospitals, the medication indent process is inefficiently handled manually using Microsoft Office tools and email. To overcome these, a digital solution called SPIREX was developed using Google Sheets and JavaScript. This tool automates the indent process between referring and receiving facilities, allowing users to generate complete, accurate indent forms that include patient information and current stock levels. These forms are sent automatically via email in PDF format to ensure data safety, timeliness, efficiency, and accuracy. Before SPIREX, issues such as low data security, time-consuming processes, and frequent medication errors resulted in poor satisfaction among patients and pharmacy staff. Data showed that only 55% of patients received complete prescriptions, and 40% did not obtain medications on time. After implementation, patient satisfaction increased from 65% to 89%, staff satisfaction rose from 60% to 85%, and medication fulfillment and timeliness improved to 90% and 92% respectively. The average time to manage SPUB orders decreased from 3 hours 40 minutes to just 1 hour. SPIREX has since been replicated in 12 health clinics and 1 hospital across Kedah, with no additional cost.